2013
DOI: 10.1017/s0266267113000175
|View full text |Cite
|
Sign up to set email alerts
|

Whose Impartiality? An Experimental Study of Veiled Stakeholders, Involved Spectators and Detached Observers

Abstract: We present an experiment designed to investigate three different mechanisms to achieve impartiality in distributive justice. We consider a first-person procedure, inspired by the Rawlsian veil of ignorance, and two third-party procedures, an involved spectator and a detached observer. First-person veiled stakeholders and involved spectators are affected by an initially unfair distribution that, in the stakeholders' case, is to be redressed. We find substantial differences in the redressing task. Detached obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 34 publications
(37 reference statements)
0
24
0
Order By: Relevance
“…3 Importantly, this third-party impartiality procedure is not equivalent to the Rawlsian "veil of ignorance" (Rawls 1971), because spectators' earnings in the experiment are completely unrelated to their allocation decisions. We deliberately did not choose a "behind the veil of ignorance" approach because it has been shown that the type of uncertainty entailed by the veil of ignorance influences individuals' allocation behavior by introducing insurance purposes (Aguiar et al 2010, Schildberg-Hörisch 2010 and strategic considerations (Gerber et al 2014). there is no uncertainty for both recipients, we expect all spectators to choose the equal split. However, will this also be the case when a recipient is exposed to uncertainty?…”
Section: Introductionmentioning
confidence: 99%
“…3 Importantly, this third-party impartiality procedure is not equivalent to the Rawlsian "veil of ignorance" (Rawls 1971), because spectators' earnings in the experiment are completely unrelated to their allocation decisions. We deliberately did not choose a "behind the veil of ignorance" approach because it has been shown that the type of uncertainty entailed by the veil of ignorance influences individuals' allocation behavior by introducing insurance purposes (Aguiar et al 2010, Schildberg-Hörisch 2010 and strategic considerations (Gerber et al 2014). there is no uncertainty for both recipients, we expect all spectators to choose the equal split. However, will this also be the case when a recipient is exposed to uncertainty?…”
Section: Introductionmentioning
confidence: 99%
“…Other studies which have considered the distributive justice preferences of individuals have typically conducted the research using students as participants [34][35][36]. Faravelli [34] finds that the selection of a particular distribution is related to the type of university course the respondent is enrolled in (i.e.…”
Section: B Utilitarianismmentioning
confidence: 99%
“…However, Konow [35] finds no evidence that personal characteristics can be used as predictors of distributive preferences. Aditionally, Aguiar et al [36] finds that the social preferences of participants do not affect individuals' decisions under impartiality conditions.…”
Section: B Utilitarianismmentioning
confidence: 99%
“…We deliberately did not choose a 'behind the veil of ignorance' approach because it has been shown that the type of uncertainty entailed by the veil of ignorance influences individuals' allocation behavior by introducing insurance purposes (Aguiar et al 2010, Schildberg-Hörisch 2010 and strategic considerations (Gerber et al 2014). equal split. However, will this also be the case when a recipient is exposed to uncertainty?…”
Section: Introductionmentioning
confidence: 99%